Links between the ornamental sector and alien plants in Southern Africa - Diana Rodríguez‐Cala; Jana Fried; John R. U. Wilson; Katharina Dehnen‐Schmutz; Seoleseng O. Tshwenyane; Israel Legwaila (Geo: Geography and Environment)
Abstract Humans and ornamental plants have a long relationship that could explain why ornamental gardening has been one of the main reasons for intentionally introducing and spreading plants worldwide. In Southern Africa, a significant part of the alien flora was introduced for ornamental purposes. Some species have become invasive, with ecological and socio‐economic impacts that can create conflicts between stakeholders, depending on their relationships with the species. This paper unpacks how the ornamental industry in Southern Africa operates as well as people's preferences for ornamental plants and practices to highlight links between the industry and plant invasions and to help address potential conflicts. Drawing on empirical data primarily collected in 2022/23 in Botswana, Namibia and Zimbabwe (and other Southern African countries), our results show that Southern Africa's ornamental industry is highly influenced by the global industry, especially South Africa. The sector provides ‘formal’ and ‘informal’ jobs to people in urban areas, especially middle‐aged women from ethnic majorities. The sector's operation and gardening practices show expressions of the typical cultural hybridity of postcolonial states where hegemonic and subaltern practices coexist and mix. Alien plants and foreign styles often symbolise higher social status, but controversially, socially privileged groups are publicly leading shifts towards more geographically contextualised practices and native plants. We conclude by arguing that recognising the influences that historical processes have on the sector's operation and its links with alien plants is essential for a more ethically sound and fair stakeholder engagement in preventing and managing plant invasions from the ornamental industry in Southern Africa.